The neurochemistry of peripheral nerve regeneration - Benga, Andreea; Zor, Fatih; Korkmaz, Ahmet; Marinescu, Bogdan; Gorantla, Vijay (Indian Journal of Plastic Surgery, 2017)
Peripheral nerve injuries (PNIs) can be most disabling, resulting in the loss of sensitivity, motor function and autonomic control in the involved anatomical segment. Although injured peripheral nerves are capable of regeneration, sub-optimal recovery of function is seen even with the best reconstruction. Distal axonal degeneration is an unavoidable consequence of PNI. There are currently few strategies aimed to maintain the distal pathway and/or target fidelity during regeneration across the zone of injury. The current state of the art approaches have been focussed on the site of nerve injury and not on their distal muscular targets or representative proximal cell bodies or central cortical regions. This is a comprehensive literature review of the neurochemistry of peripheral nerve regeneration and a state of the art analysis of experimental compounds (inorganic and organic agents) with demonstrated neurotherapeutic efficacy in improving cell body and neuron survival, reducing scar formation and maximising overall nerve regeneration.
Keywords: Cell body; nerve regeneration; nerve repair; neuron survival; peripheral nerve injury